2019
DOI: 10.18203/2394-6040.ijcmph20191428
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of a nutrition rehabilitation centre in a tertiary care hospital in Eastern India

Abstract: WHO)-UNICEF-World Bank (2015) joint estimate indicates that globally, the numbers of under-five children with wasting have remained high between 1990 and 2014, with the largest proportions of wasted children living in Asia (68.0%) and Africa (28.0%). 2 Odisha has a total population of approximately 42 million and an under-five population of approximately 3.7 million. According to the NFHS -4 conducted in 2015-16, at the national level severely wasted children comprise ABSTRACT Background: Severe acute malnutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…Overall, an improvement in the anthropometric indicators following therapy at MTC was noted in the under-5 children with SAM although the effect size was modest. Similar findings were observed in other Indian studies that also reported a statistically significant increase in weight from the time of admission to discharge at the MTC/NRC [ [8] , [9] , [10] , [11] , [12] ]. Taneja et al found a statistically significant difference between the weight (t=14.552, P < 0.001) and MUAC (t = 9.548, P < 0.001) of children irrespective of gender at admission and discharge in a study that included data from 100 SAM-affected children admitted to seven different NRCs from the state of Madhya Pradesh in India.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, an improvement in the anthropometric indicators following therapy at MTC was noted in the under-5 children with SAM although the effect size was modest. Similar findings were observed in other Indian studies that also reported a statistically significant increase in weight from the time of admission to discharge at the MTC/NRC [ [8] , [9] , [10] , [11] , [12] ]. Taneja et al found a statistically significant difference between the weight (t=14.552, P < 0.001) and MUAC (t = 9.548, P < 0.001) of children irrespective of gender at admission and discharge in a study that included data from 100 SAM-affected children admitted to seven different NRCs from the state of Madhya Pradesh in India.…”
Section: Discussionsupporting
confidence: 91%
“…The mean weight and MUAC at admission and discharge, for boys and girls separately, were found to differ statistically significantly [ 12 ]. Similar findings were observed in a study by Panda et al which included 353 Children with SAM admitted to a nutrition rehabilitation centre in Cuttack, Odisha [ 8 ]. The findings from the present study corroborate that from previous studies, and also indicate, the applicability of the NRC/MTC model in low-resource settings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation